2015
DOI: 10.15171/joddd.2015.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Push-out Bond Strength of Gutta-percha to Root Canal Dentin in Single-cone and Cold Lateral Compaction Techniques with AH Plus Sealer in Mandibular Premolars

Abstract: Background and aims. The single-cone technique has gained some popularity in some European countries. The aim of the present study was to compare the push-out bond strength of gutta-percha to root canal dentin with the single-cone and cold lateral compaction canal obturation techniques.Materials and methods. The root canals of 58 human mandibular premolars were prepared using modified crown-down technique with ProTaper rotary files up to #F3as a master apical file (MAF) and divided randomly into groups A and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
5
21
0
2
Order By: Relevance
“…Bitter, et al 5 (2009) associated rhodamine with cements and observed that bond strength values were not affected by rhodamine, values were similar to those reported in the literature. The same occurred in the present study, bond strength values found here were similar to those reported in the literature 4 , 14 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bitter, et al 5 (2009) associated rhodamine with cements and observed that bond strength values were not affected by rhodamine, values were similar to those reported in the literature. The same occurred in the present study, bond strength values found here were similar to those reported in the literature 4 , 14 .…”
Section: Discussionsupporting
confidence: 93%
“…Each root was horizontally sectioned with a slow-speed water-cooled diamond saw (Buehler Isomet 2000, Lake Bluff, IL, USA) at 4, 8, and 12 mm from the apex 14 to produce 1-mm thick slices for each root region (apical, middle, and coronal).…”
Section: Methodsmentioning
confidence: 99%
“…Various experimental methods have been used to assess the quality of root canal sealing, such as fluid filtration [ 1 ], bond strength test [ 21 22 ], photo-micrographic analysis [ 2 5 16 23 24 25 ] and µCT imaging [ 4 13 26 27 ]. Above all, µCT imaging and stereoscopic microscopic methods allow the assessment of cross-sectional images of the space occupied by GP, sealer, and void.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has limitations, which include the following: poor adaptation of gutta-percha to the canal walls, spaces between gutta-percha and the sealer, and the presence of a large amount of the sealer in the apical region due to the inhomogeneous gutta-percha-sealer mass. 17 To help to overcome these limitations, the technique used in this study was the single-cone technique. A single gutta-percha master cone placed with a sealer provides a final compact mass without spaces.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ideal adhesion of the root canal filling material to the root dentin is one of the main criteria in evaluating the clinical efficacy of the obturation technique. 17 It helps to maintain the integrity of the dentin-sealer interface by resisting dislodgment and ensuring the proper function of the restored tooth. 4 The adhesion of the obturating material to the dentin walls is evaluated using bond strength testing.…”
Section: Discussionmentioning
confidence: 99%